Manajemen Pengelolaan Makanan Sehat dan Bergizi di PAUD Plus Darussalam Bojonegoro - Nurul Novitasari; Nur Aini Zaida (Universitas Al-Hikmah Indonesia, 2021)
The management of healthy and nutritious food at PAUD Plus Darussalam has been going well. The stages of healthy food management at PAUD Plus Darussalam consist of planning, organizing, implementing, and supervising. Planning, consisting of budget planning and preparation of various menus for lunch and cakes, changing the food menu once a month with the menus that students like the most. Organizing, consisting of healthy food management personnel at PAUD Plus Darussalam. The workforce is divided into three groups, namely: the management staff group, the implementing staff group, and the implementing assistant staff group. Implementation consists of purchasing food ingredients, processing food ingredients, and distributing food. The purchase of food ingredients is the responsibility of the implementing assistant. Food processing is carried out by the implementing staff. The distribution of food is carried out by the implementing staff and the students themselves according to the picket pick-up schedule. Supervision, carried out by school principals and cooks. This type of research is field research, with a qualitative research approach. Data collection techniques using observation techniques, interviews and documentation. data analysis using Miles and Huberman models. The analytical steps carried out by the researchers include: reducing data, presenting data and drawing conclusions